2005
DOI: 10.1002/clc.4960281006
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of demographic factors and clinical features on the mode of death in high-risk patients after myocardial infarction - A combined analysis from multicenter trials

Abstract: SummaryBackground: Contemporary information is lacking on the effect of demographic features and clinical features on the specific mode of mortality after myocardial infarction (MI) in the thrombolytic era.Hypothesis: The aims of this study were (1) to examine the risk and trend of a different mode of mortality (i.e., all-cause, arrhythmic, and nonarrhythmic cardiac mortality) in highrisk patients post MI with reduced left ventricular ejection fraction (LVEF) or ventricular arrhythmias; and (2) to assess the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Although in the first place some degree of causal relationship exists between diabetes and the observed cardiovascular co-morbidities, diabetes per se appeared to account only moderately for the high overall mortality among the diabetic patients dealt with in an unselected AMI population. A recent analysis of pooled data from several AMI trials reported findings in line with our observations; the predictive value of death was higher for previous MI and history of angina than for diabetes [25].…”
Section: Discussionsupporting
confidence: 91%
“…Although in the first place some degree of causal relationship exists between diabetes and the observed cardiovascular co-morbidities, diabetes per se appeared to account only moderately for the high overall mortality among the diabetic patients dealt with in an unselected AMI population. A recent analysis of pooled data from several AMI trials reported findings in line with our observations; the predictive value of death was higher for previous MI and history of angina than for diabetes [25].…”
Section: Discussionsupporting
confidence: 91%
“…We have demonstrated the prognostic values of these variables in our previous study [13]. Scores Fig.…”
Section: Data Retrievalmentioning
confidence: 94%
“…In addition, white men have the highest death rates, followed by men of other races, women of non-white races, and lastly, white women. Table 2 displays the composite hazard ratio for arrhythmic mortality for several risk factors as determined in a meta-analysis 39 of several trials (European Myocardial Infarct Amiodarone Trial, Canadian Amiodarone Myocardial Infarction Trial, Survival With Oral D-Sotalol trial, Trandolapril Cardiac Evaluation, and Dofetilide in Patients With Acute Myocardial Infarction and Left Ventricular Dysfunction Trial). These data indicate that traditional risk factors are important predictors of arrhythmic (and sudden cardiac) death in the post-MI setting among patients with ejection fractions (EFs) of less than 35% or premature ventricular complexes.…”
Section: Risk Factors For Scdmentioning
confidence: 99%